Research progress of left-right asymmetry development in vertebrates - ZHANG Yingjie; XU Pengfei (浙江大学学报. 农业与生命科学版, 2020)
In vertebrates, it is a remarkable feature that the internal organs and nervous system are asymmetrically distributed along the left-right axis. As same as the anterior-posterior and dorsal-ventral axes, left-right asymmetry is established progressively during the early developmental stage. Left-right asymmetry development is induced by the conserved Nodal-Pitx2 signal. The concrete process includes the breaking of the symmetry, the establishment and maintenance of asymmetric signal, and the position of the eventual organ. The recent progress in left-right asymmetry development was reviewed. And recent researches have explored the establishment of left-right axis using model organisms such as mouse, zebrafish, Xenopus, etc., which help us deeply understand this developmental process.